DIGITAL TRANSFORMATION OF OUT-OF-SCHOOL EDUCATION - Marchenko , Valentyna; Yefremova , Anna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
The article is devoted to the problems and prospects of digitalization of the educational process, the importance of developing the digital competence of teachers.